Express computer the IT business news magazine. (Mumbai : Indian Express Newspapers (Bombay) Ltd.)
With reference to India.
Vol. 11, no. 10 (15 May, 2000); title from cover.
Keywords: Computer industry -- India -- Periodicals; Information services industry -- India -- Marketing -- Periodicals; Computer industry; India; Electronic journals